Gli Atti apocrifi di Marco - Lusini, Gianfrancesco (Aethiopica, 2009)
The apocryphal Acts of Mark (Gädlä Marqos) were translated from Greek in Ethiopic in the last years of the reign of ʿEzana, between 360 and 370. They are transmitted only by two manuscripts: EMML 1763, ff. 224–227 (=A), dated 1336/37 or 1339/40 and pub-lished by Getatchew Haile, “A new Ethiopic version of the Acts of St. Mark (EMML 1763, ff. 224r–227r)”, Analecta Bollandiana, 99, 1981, pp. 117–134; and Pistoia, Biblioteca Forteguerriana, ms. Martini etiop. n. 5 (= Zanutto n. 2), ff. 82–89 (= B), 18th–19th cent., recently discovered (G.L., “I codici etiopici del Fondo Martini nella Biblioteca Forte-guerriana di Pistoia”, Aethiopica, V, 2002, pp. 156–176, pp. 171–175). A new critical edition of the text of Gädlä Marqos is given here, together with a study of the Christian Ethiopian literature of the Axumite age.